Robust, fit-for-purpose method transfer: why we should apply equivalence testing. (April 2015) - Wieling, Jaap
Efficient method transfer is the key in advancing drug candidates through development and requires careful planning and communication between the two laboratories. Successful transfers require robust bioanalytical methods that allow for some small deviations from the method in sender laboratory; however, by keeping the fundamentals of the sender method intact. The equivalence of data produced at both sides should be tested by mutually prepared and analyzed QCs and by analyzing incurred samples at both sides and assessed by a statistical equivalence testing. Current regulatory bodies' guidances provide very limited direction for experimental setup and evaluation of transfer. This perspective paper gives an overview of the available approaches and proposes a way forward for the bioanalytical community.